Alpha-Synuclein Expression in Acute Erythroleukaemia, Acute Megakaryoblastic Leukemia, and Normal Counterparts in Bone Marrow - Farid Kosari; Sanam Akbarzadeh; Hiva Saffar (Iranian Society of Pathology, 2017)
Background:Alpha-synuclein is a member of synuclein family of proteins with unidentified function localized in the cytoplasm, mitochondria of neurons, and presynaptic nerve endings. Although it is found in the Lewy bodies in synucleinopathies and in Alzheimer's disease, the protein could also be considered as a novel marker in diagnosis of diseases related to the hematopoietic system. Methods: The current study evaluated alpha-synuclein expression in bone marrow sections obtained from 9 patients with acute myeloblastic leukemia (AML)-M6, 2 patients with AML-M7, and 56 patients with other forms of AML by immunohistochemical (IHC) analysis Results: Seven out of 9 cases with erythroleukemia (66.7%) and 1 of the 2 cases with M7 (50%) were positive. In contrast; the blasts in 2 out of 56 AML cases with non-M6/M7 (3.6%) showed positive staining. Accordingly, alpha-synuclein was positive in normal erythroid precursors and megakaryocytes (if existing) in these cases; while, it was negative in lymphoid and myeloid precursors. Conclusion: Alpha-synuclein expression in non-neoplastic and neoplastic erythroid cells and megakaryocytes could be used as a complementary and useful marker for distinction between AML-M6/M7 and other types of AML